THE MERIT OF YOUR HIGH GRADE IS IN YOUR COLOR OF SIN Racial microaggressions in higher education - da Silva, Edson Aparecido; da Silva, Guilherme Henrique Gomes [UNESP] (Universidade Federal de Sao Paulo, 2023)
Racial microaggressions are subtle, veiled, and indirect degradations and humiliations that are often unintentionally or not directed towards individuals at a local and individual level. Research in higher education highlights that experiences with microaggressions have caused students to abandon their programs. In this study, we aim to understand how Black students, beneficiaries of affirmative action in Science, Technology, Engineering, and Mathematics (STEM) programs, experience racial microaggressions during their university journey. To achieve this, we present results related to one analytical category of an ongoing research project, focusing on the experiences of 40 male and female Black STEM students with racial microaggressions within an academic context. The respondents encountered racial microaggressions in classrooms, laboratories, field activities, and interactions with faculty, which led to feelings of belittlement, exclusion, disregard, invalidation, and invisibility. When faced with these experiences, the students either confronted or did not confront this phenomenon through individual confrontation, group confrontation, representation, professional support, or silence.
EL MÉRITO DE TU ALTO GRADO ESTÁ EN TU COLOR DE PECADO Microagresiones raciales en la educación superior
“O MÉRITO DA SUA NOTA ALTA ESTÁ NA SUA COR DO PECADO” MICROAGRESSÕES RACIAIS NO ENSINO SUPERIOR
Keywords: math education; microaggressions; university education